Induction of Plasmodium falciparum strain 2300 dormant forms by artemisinin - Lilik Maslachah; Yoes Prijatna Dachlan; Chairul A. Nidom; Loeki Enggar Fitri (Faculty of Medicine, Universitas Trisakti, 2015)
BACKGROUND The presence of Plasmodium falciparum resistance and decreased efficacy of artemisinin and its derivatives has resulted in the issue of malaria becoming increasingly complex, because there have been no new drugs as artemisinin replacements. The aims of this research were to evaluate in vitro changes in ultrastructural morphology of P. falciparum 2300 strain after exposure to artemisinin. METHODS The research used an experimental design with post test only control group. Cultures of P. falciparum 2300 strain in one control and one mutant group were treated by exposure to artemisinin at IC50 10-7 M for 48 hours. Ultrastructural phenotypic examination of ring, trophozoite and schizont morphology and developmental stage in the control and mutant group were done at 0, 12, 24, 36, 48 hours by making thin blood smears stained with 20% Giemsa for 20 minutes and examined using a microscope light at 1000x magnification. RESULTS Dormant forms occurred after 48 hours of incubation with IC50 10-7 M artemisinin in the control group. In the mutant group, dormant forms, trophozoites with blue cytoplasm and normal schizont developmental stages were seen. Ultrastructural phenotypic morphology at 0, 12, 24, 36, 48 hours showed that in the control group dormant formation already occurred with exposure to IC50 10-7 M, while in the mutant group dormant formation occurred only with exposure to IC50 2.5x10-5 M. CONCLUSION Exposure to artemisinin antimalarials in vitro can cause phenotypic morphological changes of dormancy in P. falciparum Papua 2300 strain.